#### Answer

The solution is -$\frac{7}{8}$

#### Work Step by Step

$\frac{1}{2}$ + a= -$\frac{3}{8}$
$\frac{1}{2}$+a -$\frac{1}{2}$=- $\frac{3}{8}$-$\frac{1}{2}$
Subtract $\frac{1}{2}$ to both sides
$a=-\frac{3}{8}$-$\frac{4}{8}$
LCD of the denominators 8 and 2 is 8
$a=-\frac{3}{8}$-$\frac{4}{8}$
$a=\frac{-3-4}{8}$
$a= -\frac{7}{8}$
The solution is -$\frac{7}{8}$
Check
Replace y with $\frac{-7}{8}$
$\frac{1}{2}$ +a=-$\frac{3}{8}$
$\frac{1}{2}$ -$\frac{7}{10}$=-$\frac{3}{10}$
$\frac{1}{2}$ -$\frac{7}{8}$=-$\frac{3}{8}$
$\frac{4}{8}$-$\frac{7}{8}$=-$\frac{3}{8}$
$\frac{4-7}{8}$=-$\frac{3}{8}$
-$\frac{3}{8}$=-$\frac{3}{8}$